Genetic diversity pattern reveals the primary determinant of burcucumber (Sicyos angulatus L.) invasion in Korea - Lee, Soo-Rang; Son, Dong Chan (Frontiers in Plant Science, 2022)
Biological invasion is a complex process associated with propagule pressure, dispersal ability, environmental constraints and human interventions, which leave genetic signatures. Population genetics of an invasive species, thus provides invaluable insights into the patterns of invasion. Burcucumber, one of the most detrimental weeds for soybean production in US, has recently colonized Korea and rapidly spread posing a great threat to the natural ecosystem. We aim to infer the determinants of the rapid burcucumber invasion by examining the genetic diversity, demography and spread pattern with advanced genomic tools. We employed 2696 genome-wide single nucleotide polymorphisms to assess the level of diversity and the spatial pattern associated with the landscape factors and to infer the demographic changes of 24 populations (364 genotypes) across four major river basins with the east coastal streams in South Korea. Through the Approximate Bayesian Computation, we inferred the likely invasion scenario of burcucumber in Korea. Landscape genetics approach adopting circuit theory and MaxEnt model was applied to determine the landscape contributors. Our data suggested that most populations have experienced population bottlenecks, which lead to lowered within-population genetic diversity and inflated population divergences. Burcucumber colonization in Korea has strongly been affected by demographic bottlenecks and multiple introductions, whereas environmental factors were not the primary determinant of the invasion. Our work highlighted the significance of preventing secondary introductions, particularly for aggressive weedy plants such as the burcucumber.